PROFILE OF LEARNING MEDIA OF INTERACTIVE MULTIMEDIA ON MEMBRANE TRANSPORT CELL TOPIC FOR XI GRADE OF SENIOR HIGH SCHOOL - SITI SUHARTIA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
This research aimed to describe the theoretical feasibility of learning media of interactive multimedia on membrane transport cell topic based on the validation value of media. These media were validated based on three component, namely: topic, language, and presentation. The media were validated by biology lecturers and teachers. The validation value of media was 92,1%. This result showed that interactive multimedia were very feasible. Keyword: interactive multimedia, membrane transport cell, feasibility of media.